Comparison of the Clinical Outcomes between Combined Femtosecond Laser-Assisted In Situ Keratomileusis and Corneal Cross Linking versus Combined Small-Incision Lenticule Extraction and Corneal Cross Linking. (31st January 2022) - Di, Yu; Mo, Fei; Li, Ying
Abstract : Purpose . The purpose of this study was to compare femtosecond laser-assisted in situ keratomileusis with prophylactic cross linking (FS-LASIK Xtra) and small-incision lenticule extraction with prophylactic cross linking (SMILE Xtra) in terms of their postoperative clinical outcomes. Methods . In this retrospective study, 24 patients (48 eyes) with myopia and myopia astigmatism were recruited from 2017 to 2018. All patients underwent comprehensive ophthalmic examinations preoperatively and follow-up visits at one and three months. Four patients (eight eyes) in each group were followed up for 12 months. The following were assessed at each visit: uncorrected distance visual acuity (UDVA), manifest refractive spherical equivalent (MRSE), keratometry values, biomechanical properties, anterior and posterior curvature, and corneal pachymetry. Results . The FS-LASIK Xtra and SMILE Xtra groups both included 24 eyes of 12 patients. At 1, 3, and 12 months after surgery, a UDVA of 20/20 or better was achieved for 91.7%, 91.7%, and 87.5% of individuals, respectively, in the FS-LASIK group and 95.8%, 100%, and 100% in the SMILE group, respectively. For 75% of eyes in the FS-LASIK Xtra group and 100% of eyes in the SMILE Xtra group, the achieved MRSE was within ±1.00D of attempted correction. The LASIK Xtra group had a significantly higher mean MRSE than the SMILE Xtra group at 3 and 12 months after surgery (P = 0.006, 0.01 ), and the SMILE Xtra group had significantly higher K 1 and K 2 values than the FS-LASIK group at one month after surgery (P = 0.024, 0.023 ). Corneal thickness decreased significantly at one month postoperatively and started to increase over the next 12 months in both groups (P = 0.001 ). The biomechanical properties showed no significant intergroup differences at the 12-month follow-up. Conclusions . FS-LASIK Xtra and SMILE Xtra are safe and effective in the correction of myopia and myopia astigmatism, and both procedures have the same effect on postoperative corneal morphology and biomechanics.